Características biológicas de cepas de Herpesvirus bovino 1 y 5 utilizando el modelo experimental conejo - Pidone, C.L. (2012)
Bovine Herpesvirus (BoHV) can infect both rabbits and mustelids. Rabbit has been used as a laboratory model for infection with BoHV-1 and 5. The objective of this research was to study the pathogenicity of different Argentinian BoHV-1 and BoHV-5 strains by using the rabbit experimental model. New Zealand rabbits were inoculated by intranasal and intravaginal ways. The animals inoculated intranasally with strains of BoHV-5 developed neurological signs in 83% of the cases. BoHV-1.1 caused neurological signs in 57% of the animals and BoHV-1.2 did not cause clear clinical signs. BoHV-5 caused nervous signs in young animals while BoHV-1 did so occasionally in young rabbits. Animales inoculated intravaginally showed no apparent clinical signs or apparent lesions in the studied organs. The infection was demonstrated by serological seroconversion. The rabbit was appropriate to study the clinical signs and the lesions produced in the different organs, primarily in the central nervous system. The model was useful for being inexpensive and very easy to use, and it enabled to identify differences in the biological behavior of the studied BoHV-1 and BoHV-5 strains.